2017
DOI: 10.1159/000479877
|View full text |Cite
|
Sign up to set email alerts
|

Peripapillary Choroidal Thickness Analysis Using Swept-Source Optical Coherence Tomography in Glaucoma Patients: A Broader Approach

Abstract: Aims: To evaluate and compare peripapillary choroidal thickness (PPCT) in a wide area around the optic disk and various choroidal established zones in healthy controls and primary open-angle glaucoma (POAG) patients using a new swept-source (SS) optical coherence tomography (OCT) device. Methods: A total of 246 eyes were finally included in this observational, prospective, cross-sectional study: 111 healthy controls and 135 POAG patients. The healthy subjects were divided into 2 populations: the teaching popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…This result emphasizes that the evaluation of RNFLI thickness in the early stages of glaucoma may be an important parameter concerning follow-up. In a study evaluating peripapillary CT in glaucoma cases, the CT in the inferior quadrant was found to be thinner than others (21). This result supports our conclusion that the inferior quadrant is the first affected quadrant.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This result emphasizes that the evaluation of RNFLI thickness in the early stages of glaucoma may be an important parameter concerning follow-up. In a study evaluating peripapillary CT in glaucoma cases, the CT in the inferior quadrant was found to be thinner than others (21). This result supports our conclusion that the inferior quadrant is the first affected quadrant.…”
Section: Discussionsupporting
confidence: 83%
“…However, in recent years, peripapillary choroidal thickness measurements have been performed. Due to these measurements, significant changes and their correlations between ocular parameters were observed in glaucoma (21,22). Many previous reports have suggested that no association between GON and subfoveal CT exists (23,24).…”
Section: Discussionmentioning
confidence: 84%
“…However, the accuracy of depicting choroid layer declined in the extremely thick group in this study, a finding that has also been previously reported. Ophthalmologists have put focus on pathophysiology between choroid layer and various ocular diseases ranging from anterior segment (keratoconus, glaucoma) to posterior segment (AMD, PCV, optic neuropathy) [29][30][31][32][33][34]. Through the experimental thirty cases in our study, the feasibility of this Mask R-CNN model has been proved.…”
Section: Discussionmentioning
confidence: 84%
“…Recent clinical studies suggest that the contribution of the choroid to the pathophysiology of a range of ocular diseases such as age-related macular degeneration 22 , central serous chorioretinopathy 23 , and glaucoma 24 are not restricted to the macular region. However, in the absence of normative thickness data for the peripheral choroid, it is difficult to attribute changes in peripheral choroidal thickness solely to disease processes.…”
Section: Introductionmentioning
confidence: 99%